Speech-Language Therapy classroom-based language intervention: A Scoping Review - Pozo Tapia, Francisca; Mendive Criado, Susana (Revista de Investigación en Logopedia, 2026)
Speech-language pathology intervention in the regular classroom is crucial for supporting children with reduced linguistic abilities, as it prevents more significant difficulties and allows for a broader generalization of skills and collaboration with teachers. However, the lack of systematized information on the available evidence of these practices hinders their effective implementation and the creation of clear guidelines. This review aims to synthesize the evidence on the effectiveness of speech-language pathology interventions in the regular classroom for children aged 3 to 12 years. We searched articles published between 2000 and 2020 in English or Spanish in WoS and Scopus. The results yielded 19 studies that met the criteria. These interventions were characterized according to their level of evidence, language skill, service delivery model, dosage, and age of the children. The evidence indicates that classroom work on phonological awareness, vocabulary, simple grammatical comprehension and expression, and narrative production is effective. High-quality studies support this, but there is still a need for further research on interventions that support other relevant skills. This review identifies available evidence and guides practice in implementing effective strategies for linguistic skills in the regular classroom.
Keywords: Classroom; Education; Service delivery models; Speech and language therapy; Speech language and communicational needs